Cost Effective 3D Printed Device for Tuberculosis Nanoformulation Manufacturing. (29th May 2018) - Chan, Lorene; Nguyen, Ai; Bokare, Anuja; Erogbogbo, Folarin
Abstract: A 3D printed device has been developed for cost-effective production of rifampicin loaded lipid polymer hybrid nanoparticles. These nanoparticles show considerable potential for research related to the treatment of Tuberculosis. The nanoparticles synthesized by the device possess a core-shell drug-lipid polymer assembly. The synthesis conditions have been optimized with respect to the parameters like flow-rate, size of device, and the concentration of rifampicin and poly lactic-co-glycolic acid (in which the drug molecules are incorporated). The nanoparticles synthesized by the 3D printed device yield smaller nanoparticles with narrow size distributions in contrast to traditional sonication method. The device can be operated either by hand or by using syringe pumps. These nanoparticles also show excellent antibacterial activity which typically correlates with a reduction in drug dosing frequency to promote patient adherence to drug regimens.